PRINCIPAL MANAGEMENT STRATEGIES IN INCREASING STUDENT LEARNING MOTIVATION DURING THE PANDEMIC - Agustina, Ike Yama (Sekolah Tinggi Ilmu Tarbiyah (STIT) Al-Ishlah Bondowoso, 2022)
Schools as educational institutions are tasked with organizing the educational process and teaching and learning process in an effort to educate the nation's life. In this case, the principal is given the task of leading the school and is responsible for achieving the school's goals. The purpose of this research is to find out how the principal's leadership strategy in realizing the quality of madrasah by increasing the learning motivation of its students. This research is a descriptive qualitative research with a phenomenological approach that occurs in the field. Data collection used observation, in-depth interviews and documentation. The data analysis technique uses three lines of analysis, namely data reduction, data presentation and verification. The results of this study indicate that: the strategy carried out by the principal in increasing student motivation is in 3 ways: first, improving facilities and infrastructure or school facilities during pandemic learning, such as adding wifi networks and increasing the number of computers. Second, improving teacher resources by facilitating and providing training related to distance learning and providing an injection of funds for distance learning which is carried out independently by teachers at home. Third, developing students' potential in the field of science and technology as a motivation for students to continue to be enthusiastic about learning and participating in the learning process.